The economic impact of a COVID-19 illness from the perspective of families seeking care in a private hospital in India - Tarun K. George; Parth Sharma; Melvin Joy; Guna Seelan; Abirami Sekar; Karthik Gunasekaran; Kundavaram Paul Prabhakar Abhilash; Tina George; Sudha Jasmine Rajan; Samuel George Hansdak (Elsevier, 2023)
Background: The Covid-19 pandemic had a tremendous impact that caused significant morbidity, mortality, and financial stress for families. Our study aimed to determine the Out-of-pocket expenses and economic impact of a Covid-19 illness for households where patients were admitted to a private hospital in India. Methodology: This was a cost-of-illness study from a tertiary care academic institute where adult patients diagnosed with COVID-19 from May 2020 to June 2021 were included. Patients with an admission of less than one day or who had any form of insurance were excluded. The clinical and financial details were obtained from the hospital information system and a cross-sectional survey. This was stratified across three clinical severity levels and two epidemiological waves. Results: The final analysis included 4445 patients, with 73 % admitted in Wave 1 and 99 patients interviewed. For patients with severity levels 1, 2 and 3, the median admission days were 7, 8 and 13 days respectively. The total cost of illness (general category) was $934 (₹69,010), $1507 (₹111,403) and $3611 (₹266,930) and the direct medical cost constituted 66%, 77% and 91% of the total cost for each level respectively. Factors associated with higher admission costs were higher age groups, male gender, oxygen use, ICU care, private admission, increased duration of hospital stay and Wave 2. The median annual household income was $3247 (₹240,000) and 36% of families had to rely on more than one financial coping strategies, loans with interest being the commonest one. The lockdown period affected employment and reduced income for a considerable proportion of households. Conclusion: A Covid admission of higher severity was a significant financial burden on families. The study reaffirms the need for collaborative and sustainable health financing systems to protect populations from hardships.$-US Dollar; ₹- Indian Rupees